Happiness at Work in the Context of Javanese and Chinese Workers - Yonathan Setyawan; Robik Anwar Dani; Andi Cahyadi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
This study aims to describe the differences in happiness at work between Javanese workers and Chinese workers in Madiun City. The subjects in this study consisted of 100 workers of Javanese origin and 100 workers of Chinese origin working in Madiun City. The methodology applied in this study uses a quantitative approach, while the measuring instrument used is the happiness at work scale developed by Salas-Vallina, A., and Alegre, J. (2021). The results of this study show that there is no difference in happiness at work between Javanese workers and Chinese workers in Madiun City, which can be seen from the sig. or P value of 0.353, which is greater than 0.05. Happiness at work for Javanese and Chinese workers in Madiun City is recorded in the medium category, with a percentage of 57% for Javanese workers and 59% for Chinese workers. Although there is no difference, there are variations in the factors that contribute to happiness at work; namely, for Javanese workers, it is more likely to be on the social aspect with a percentage of 44%, while Chinese workers are more on the psychological aspect with a percentage of 72%. Penelitian ini bertujuan untuk menggambarkan perbedaan happiness at work antara pekerja Jawa dan pekerja Tionghoa yang ada di Kota Madiun. Subjek dalam penelitian ini terdiri dari 100 pekerja yang berasal dari suku Jawa dan 100 pekerja dari suku Tionghoa yang bekerja di Kota Madiun. Metodologi yang diterapkan dalam penelitian ini menggunakan pendekatan kuantitatif, sementara alat ukur yang digunakan adalah skala happiness at work yang dikembangkan oleh Salas-Vallina, A., dan Alegre, J. (2021). Analisis data yang digunakan adalah uji perbedaan Mann-Whitney dengan bantuan perangkat lunak IBM 23. Hasil dari penelitian ini menunjukkan tidak terdapat perbedaan happiness at work antara pekerja suku Jawa dan pekerja suku Tionghoa di Kota Madiun, yang dapat dilihat dari nilai sig. atau P Value sebesar 0,353 yang lebih besar dari 0,05. Kebahagiaan di tempat kerja bagi pekerja Jawa dan pekerja Tionghoa di Kota Madiun tercatat dalam kategori sedang, dengan persentase 57% untuk pekerja Jawa dan 59% untuk pekerja Tionghoa. Meskipun tidak ada perbedaan, terdapat variasi dalam faktor-faktor yang menyumbang happiness at work, yakni bagi pekerja Jawa lebih cenderung pada aspek sosial dengan persentase 44%, sedangkan pekerja Tionghoa lebih pada aspek psikologis dengan persentase 72%.